Sistem Pendukung Keputusan dalam Pemilihan Mobil menggunakan Metode Analytical Hierarchy Process (AHP) - fajar sidiq; Fattya Ariani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2022)
Along with the development of automotive technology and computer technology, the car which is one form of transportation also receives the impact of these developments. In today's cars, additional features are available that apply a combination of the two technologies above. In connection with the above, consumers who in this case are those who will buy a car and use car facilities more or less will feel the impact of the existence of several types of cars, each of which has different specifications. Environmental factors can influence the choice of a car based on the size of the car and the capacity of passengers and luggage. The most visible impact due to the problems above is the emergence of confusion in making choices when buying a car. Based on these problems, a decision support system for buying a car was built which aims to make it easier and faster for prospective car buyers to determine which one to buy. The method applied in building a decision support system is the analytic hierarchy process (AHP) method